The Denominations of Metaphysics and its Science in the Late Antique Philosophy - Napoli, Valerio (Peitho. Examina Antiqua, 2012)
In late antiquity, in the context of the jagged tradition of Neo-Platonism, Aristotle’s Metaphysics and the specific science that is traced out in it are indicated with the current denominations of meta ta physika and theologikē pragmateia, which are seen as consistent with one another and closely interconnected. In this connection, the Metaphysics, in the wake of previous philosophical readings, is considered as a treatise on “theological science” — the most elevated among the sciences — and the denomination meta ta physika is seen in a specifically theological sense. According to a widespread Neo-Platonic reading, the science thematized in the Metaphysics is “metaphysics” in that it is theological science, an epistemic discourse on divine realities, which, within the ordo rerum, transcend the physical ones, and, therefore, according to the ordo cognoscendi, must be studied after the latter.